Anxiety Disorder: Inconsistency and Agitation in Yrsa Sigurdardordottir’s Novel “Why Did You Lie?” - Adli Faishal Hakim; Rahmi Rivalina (Morphosis: Journal of Literature, 2023)
This study entitled “Anxiety Disorder : Inconsistency and Agitation in Yrsa Sigurdardordottir’s Why Did You Lie? (2016)” was conducted to study further based on the perspective of the main character in Why Did You Lie? in fighting Anxiety disorder that he experienced throughout his daily life. The aim of this study is to analyze the issue of anxiety disorder on the object of the study Yrsa Sigurdardordottir’s Why Did You Lie? (2016). This study focuses on explaining the portrayals of anxiety disorder in the main character. This study applies the theory of anxiety disorder by Sigmund Freud from his book entitled: Introduction to Psychoanalysis (1917). This study was conducted using the qualitative method by Creswell (1994). The result display that anxiety disorder in forms of thought and action and how the main character deals with the anxiety. This is a part of the analysis that appear in this study. The results of this study show how the main character depicted Anxiety Disorder through actions and thought. Keywords: anxiety disorder, inconsistency, agitation, psychoanalysis